2020
DOI: 10.1111/apha.13436
|View full text |Cite
|
Sign up to set email alerts
|

The hypoxia tolerance of eight related African mole‐rat species rivals that of naked mole‐rats, despite divergent ventilatory and metabolic strategies in severe hypoxia

Abstract: Aims Burrowing mammals tend to be more hypoxia tolerant than non‐burrowing mammals and rely less on increases in ventilation and more on decreases in metabolic rate to tolerate hypoxia. Naked mole‐rats (Heterocephalus glaber, NMRs), eusocial mammals that live in large colonies, are among the most hypoxia‐tolerant mammals, and rely almost solely on decreases in metabolism with little change in ventilation during hypoxia. We hypothesized that the remarkable hypoxia tolerance of NMRs is an evolutionarily conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 60 publications
6
50
3
Order By: Relevance
“…The comparison between these two mole-rats species and other subterranean rodents, other partial fossorial mole-rat species, also shows a reduced BMR by more than 29% [38]. The observed lower BMR might be explained by their fully fossorial lifestyle and eusocial colony organization which likely results in repeated exposure to severe hypoxia [18]. Interestingly, while age-related declines in BMR in disease-free individuals are extensively documented feature in human and laboratory rodent species [57,58], we observed no detectable age-related declines in body mass (Mb) and BMR in DMR or the NMR [41].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The comparison between these two mole-rats species and other subterranean rodents, other partial fossorial mole-rat species, also shows a reduced BMR by more than 29% [38]. The observed lower BMR might be explained by their fully fossorial lifestyle and eusocial colony organization which likely results in repeated exposure to severe hypoxia [18]. Interestingly, while age-related declines in BMR in disease-free individuals are extensively documented feature in human and laboratory rodent species [57,58], we observed no detectable age-related declines in body mass (Mb) and BMR in DMR or the NMR [41].…”
Section: Discussionmentioning
confidence: 83%
“…Such observations directly challenge the most prominent life-history trade-off, the cost of reproduction at the expense of somatic maintenance resulting in a negative association between reproductive output and longevity [17]. More impressively, besides their extreme longevity and high reproductive output, both these species also share other characteristics such as hypoxia tolerance [18] and tolerance of oxidative stress [19], features considered evolved traits in response to life below ground for millenia [20]. In spite of the similarities of these exceptional life history traits within this monophyletic clade [21], NMR and DMR exhibit fundamental differences in their evolutionary history: studies suggest they evolved eusociality independently [22,23], and have divergent physiological responses to different stressors [23].…”
Section: Introductionmentioning
confidence: 99%
“…Free radicals are also produced upon reoxygenation. However, several mole-rat species such as Spalax galili and Heterocephalus glaber are resistant to decreases in oxygen tension (Larson and Park, 2009;Schülke et al, 2012;Shams et al, 2004), and other species of African mole-rats (Bathyergidae) may also show hypoxia tolerance (Ivy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Eusocial burrowing animals need hypoxia tolerance to suit their lifestyle preferences. 24 Lastly, Olson et al found that cellular H 2 S is increased during extended hypoxia, probably functioning as a continuously active O 2 -sensing mechanism in several cells. 25 Protection from detrimental environmental influences has, without doubt, contributed to modern man living longer and healthier lives than ever before in human history.…”
Section: Environment and Exposurementioning
confidence: 99%
“…Insufficient oxygen availability is, however, not exclusively a pathological phenomenon. Eusocial burrowing animals need hypoxia tolerance to suit their lifestyle preferences 24 . Lastly, Olson et al found that cellular H 2 S is increased during extended hypoxia, probably functioning as a continuously active O 2 ‐sensing mechanism in several cells 25 …”
mentioning
confidence: 99%